2016
DOI: 10.1016/j.aogh.2015.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned from Implementing a Rapid Test of a Technology Device in a Tertiary Hospital in Uganda

Abstract: A rapid study of innovative technology can be successful at a hospital in a resource-limited setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…A review of the current literature shows that only four studies have evaluated any form of wireless wearable technology in LMIC settings: one pilot study (conducted by two of this study’s authors) evaluating the use of a wearable device in patients with suspected Ebola virus disease in Sierra Leone; and three studies in Uganda—two in a maternity ward and one in a general medical ward. 20,26,32,33 While no prior studies have evaluated wireless wearable devices for pediatric monitoring in an LMIC setting, the findings of this study urge further investigation of these devices in pediatric patients who constitute a large burden of critically ill patients in LMICs. A recent study among pediatric inpatients admitted to district-level hospitals in Kenya found that the frequency of vital sign measurements was far lower than the stated goal benchmark of three sets of vital sign measurements in a 24-h period.…”
Section: Discussionmentioning
confidence: 91%
“…A review of the current literature shows that only four studies have evaluated any form of wireless wearable technology in LMIC settings: one pilot study (conducted by two of this study’s authors) evaluating the use of a wearable device in patients with suspected Ebola virus disease in Sierra Leone; and three studies in Uganda—two in a maternity ward and one in a general medical ward. 20,26,32,33 While no prior studies have evaluated wireless wearable devices for pediatric monitoring in an LMIC setting, the findings of this study urge further investigation of these devices in pediatric patients who constitute a large burden of critically ill patients in LMICs. A recent study among pediatric inpatients admitted to district-level hospitals in Kenya found that the frequency of vital sign measurements was far lower than the stated goal benchmark of three sets of vital sign measurements in a 24-h period.…”
Section: Discussionmentioning
confidence: 91%
“…The accuracy of the EarlySense device was confirmed in a study population of high-risk adult surgical patients and in a small feasibility series with a paediatric and adult patient population in a sleep laboratory and intensive care unit setting. 21 22 Other studies of monitoring technologies have been conducted in low-resource settings [23][24][25][26] ; however, research conducted in neonates has largely been limited to studies in high-resource settings. Well-established methods for HR and RR monitoring exist, but limitations including inaccuracy, invasiveness, timeconsuming application and high cost have prompted development of novel technologies.…”
Section: Global Child Healthmentioning
confidence: 99%